Bling bling taxation and the fiscal virtues of hip hop - Per Engström (Uppsala University, Department of Economics, 2010)
The paper extends Ng's (1987) model of optimal taxation of diamond goods - goods that are valued solely for their costliness. We extend his findings by analyzing how other goods should be taxed in the presence of pure diamond goods; modified Ramsey rules are derived in a basic single-type model as well as in a two-type model with redistribution. One key finding, that may be surprising and rather provoking, is that close complements (hip hop music) to diamond goods (bling bling) should be heavily subsidized.
urn:nbn:se:uu:diva-129536
Keywords: H20; H21; 330; optimal taxation; status; luxury taxation; Optimale Besteuerung; Spezielle Verbrauchsteuer; Sozialer Status; Theorie